2022
DOI: 10.3389/fmolb.2022.925404
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic recognition of naloxone, morphine and endomorphin1 in the same pocket of µ-opioid receptors

Abstract: Morphine, the most widely used analgesic, relieves severe pain by activating the μ-opioid receptor (MOR), whereas naloxone, with only slight structural changes compared to morphine, exhibits inhibitory effect, and is used to treat opioid abuse. The mechanism by which the MOR distinguishes between the two is unclear. Molecular dynamics (MD) simulations on a 1-μs time scale and metadynamics-enhanced conformational sampling are used here to determine the different interactions of these two ligands with MOR: morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…To further verify at the cellular level whether morphine reduces macrophage phagocytosis of tumors at therapeutic doses, we induced THP-1 cells into phagocytic macrophages with phorbol-12-myristate-13-acetate (PMA), followed by A549 cells labeled with the fluorescent dye probe Protonex TM Red 600, and co-cultured with macrophages for 24 h. The results were obtained by fluorescence intensity recorded by fluorescence microscopy photographs, and morphine at 10 nM significantly attenuated phagocytosis of A549 by macrophages compared to the controls (13.1 ± 3.2% vs. 34.7 ± 4.6%, 10 nM morphine vs. Ctrl, respectively, p < 0.01, n = 3, unpaired t -test, Figure 1 A,B). Additionally, the phagocytosis of A549 by macrophages was examined by flow cytometry in the concentration range of 0.001 nM~10 μM, and it was found that morphine concentration dependently inhibited the phagocytic effect of macrophages (EC 50 (concentration producing half the efficacy) = 2.13 ± 0.16 nM, Figure 1 C), which is the concentration required for morphine to activate MOR [ 33 ], indicating that direct inhibition of tumor phagocytosis by macrophages at nM levels of morphine is a possible phenomenon during clinical administration.…”
Section: Resultsmentioning
confidence: 99%
“…To further verify at the cellular level whether morphine reduces macrophage phagocytosis of tumors at therapeutic doses, we induced THP-1 cells into phagocytic macrophages with phorbol-12-myristate-13-acetate (PMA), followed by A549 cells labeled with the fluorescent dye probe Protonex TM Red 600, and co-cultured with macrophages for 24 h. The results were obtained by fluorescence intensity recorded by fluorescence microscopy photographs, and morphine at 10 nM significantly attenuated phagocytosis of A549 by macrophages compared to the controls (13.1 ± 3.2% vs. 34.7 ± 4.6%, 10 nM morphine vs. Ctrl, respectively, p < 0.01, n = 3, unpaired t -test, Figure 1 A,B). Additionally, the phagocytosis of A549 by macrophages was examined by flow cytometry in the concentration range of 0.001 nM~10 μM, and it was found that morphine concentration dependently inhibited the phagocytic effect of macrophages (EC 50 (concentration producing half the efficacy) = 2.13 ± 0.16 nM, Figure 1 C), which is the concentration required for morphine to activate MOR [ 33 ], indicating that direct inhibition of tumor phagocytosis by macrophages at nM levels of morphine is a possible phenomenon during clinical administration.…”
Section: Resultsmentioning
confidence: 99%
“…As we described previously [40] , [41] , [42] , human embryonic kidney (HEK 293) cells were purchased from Shanghai Institutes for Biological Sciences and cultured in Dulbecco's Modified Eagle Medium supplemented with 10% fetal bovine serum (FBS), 1% penicillin-streptomycin and 1% GlutaMAX™ at 37 °C, 5% CO 2 and 95% air in a humidified environment. Plasmids were transfected into cells using transfection agents containing two solutions (Solution A: 250 mM CaCl 2 in pure water; Solution B (in mM): 1.5 Na 2 HPO 4 , 140 NaCl and 50 HEPES, pH adjusted to 6.96).…”
Section: Methodsmentioning
confidence: 99%
“…The energy-minimized structures of hP2X3/TNP-ATP (PDB ID:5SVQ), ckP2X7/TNP-ATP (PDB ID:5XW6) were used as the initial structures for CMD simulations. A large 1-palmitoyl- 2-oleoyl-sn-glycero-3-phosphocholine (POPC, 300 K) bilayer, available in System Builder of DESMOND [42] , [44] , was built to generate a suitable membrane system based on the OPM database [45] . The hP2X3/TNP-ATP/POPC and ckP2X7/TNP-ATP/POPC systems were dissolved in simple point charge (SPC) water molecules.…”
Section: Methodsmentioning
confidence: 99%
“…The energy-minimized models of the PPNDS-bound pdP2X7 were used as the initial structures for MD simulations. A large 1-palmitoyl-2-oleoyl-sn-glycero-3- phosphocholine (POPC, 300 K) bilayer, available in System Builder of DESMOND 57,60 , was built to generate a suitable membrane system based on the OPM database 61 . The systems were dissolved in simple point charge (SPC) water molecules.…”
Section: Methodsmentioning
confidence: 99%
“…-17 -Human embryonic kidney 293 (HEK293) cells were purchased from Shanghai Institutes for Biological Sciences and cultured in Dulbecco's modified Eagle's medium supplemented with 10% fetal bovine serum (FBS), 1% penicillin-streptomycin, and 1% GlutaMAX™ at 37 °C in a humidified atmosphere of 5% CO2 and 95% air 55,56 . Plasmids harboring hP2X1, hP2X3 or pdP2X7 were transfected into cells by calcium phosphate transfection 57 . Currents of hP2X1 and hP2X3 were recorded using nystatin (Sangon Biotech, China) perforated recordings to prevent rundown in current during multiple dose applications of ATP.…”
Section: Electrophysiologymentioning
confidence: 99%